Impact of cellular autophagy on viruses: Insights from hepatitis B virus and human retroviruses - Tang, Sai-Wen (BioMed Central, 2012)
Autophagy is a protein degradative process important for normal cellular metabolism. It is apparently used also by cells to eliminate invading pathogens. Interestingly, many pathogens have learned to subvert the cell’s autophagic process. Here, we review the interactions between viruses and cells in regards to cellular autophagy. Using findings from hepatitis B virus and human retroviruses, HIV-1 and HTLV-1, we discuss mechanisms used by viruses to usurp cellular autophagy in ways that benefit viral replication.